Knowledge and Practices on HIV/AIDS among Injecting Drug Users - Prasad, Subhash (Academic Voices: A Multidisciplinary Journal, 2014)
Injecting drug use is the main route of transmission of HIV/AIDS. Injecting Drug Users (IDUs) are one of the high risk groups of this infection. This paper describes the knowledge and practice of HIV in injecting drug users based on quantitative data collected from 154 IDUs by interview schedule. It is concluded that the knowledge about HIV/AIDS amongst the injecting drug users is not a problem. The key problem is sharing used syringe by some users to take drugs to fulfill their urgent compulsion. The gap between knowledge and practice causes them to the vulnerability of the problem. Academic Voices, Vol. 3, No. 1, 2013, Pages 62-67 DOI: http://dx.doi.org/10.3126/av.v3i1.9990